Anti-Liberalism: Historical Comparison, Rhetoric, and Politics - Rosales, José María (EDUCatt, 2023)
Anti-liberalism is both a kind of rhetoric and of politics. This chapter presents some of their distinct features. Looking at recent cases in Europe invites a comparison with the past through the early decades of the twentieth century. Similarities and differences can be observed, but as an exploratory method, historical comparisons provide limited knowledge that needs to be enriched with insights into current examples of anti-liberal rhetoric and politics. They no longer come from young, unstable democratic regimes but from consolidated democracies. This significant difference suggests a revision of the standard or traditional view about anti-liberalism.
Política de acceso abierto: https://www.polidemos.it/codice-etico/ Gli articoli sono pubblicati in Platinum Open Access, ovvero NON sono applicati submission fee né APC (Article Processing Charges). La pubblicazione di articoli è dunque completamente gratuita perché Polidemos aderisce alle policy di open access, pubblicando i suoi articoli sotto la licenza Creative Commons Attribution (CC-BY-NC-SA).
Civic Constellation III: Democracy, Constitutionalism, and Anti-Liberalism research project (PGC2018-093573-B-100, 2019-2022) (https://www.uma.es/civicconstellation)
Keywords: Democracia - Países de la Unión Europea; Populismo; Política y gobierno; Anti-liberalism; Political rhetoric; Emergency rule; European democracies; Parliamentarism; Populism